Adaptação transcultural da escala Coming out Growth - Sena, Ana Aparecida Lopes (Brasil, 2024)
Introduction: The coming out process is made up of stages such as self-acceptance, identity formation and the act of revealing your sexuality to other people. Such revelation can lead to experiences of personal and social growth, which is assessed by the Coming Out Growth Scale. General objective: Carry out a semantic adaptation of the Coming Out Growth scale for the Brazilian context. Specific objectives: (1) carry out translation and semantic adaptation of the Coming Out Growth scale; (2) present a psychometric measure that assesses personal development after revealing sexuality. Methodology: The transcultural semantic adaptation protocol of instruments was used, which consists of five stages: translation; synthesis of translations; evaluation by the committee of judges; target audience assessment; and, back-translation. Results: Most of the items on the scale had a high level of comprehensibility and good writing, as a result of the analysis of the pilot study. Furthermore, as a result of the back-translation, the items kept their meanings preserved, according to the original author.